FUNGSI TARI RAPA'I GELENG PASCA TSUNAMI DAN PASCA KONFLIK DALAM MASYARAKAT ACEH BARAT DAYA - Anton Setiabudi (Pascasarjana Institut Seni Indonesia Surakarta, 2010)
The essence of this research is to discuss about what the function of Rapaâ€™i Geleng Dance in the North West Aceh Tribe in time after tsunami and conflict are. Based on the matter, this research aims to find out the system of socio-culture of the North West Aceh Tribe specifically as a representation of the social value system in time after conflict and tsunami, (2) to describe the function of Rapaâ€™i Geleng Dance in reconstructing and rehabilitating the social regulation in the society deeply as a consequence of the conflict and tsunami happened in Aceh. A qualitative approach using the interconnection model is the contextual study of ethnochoreology, sociology, and anthropology. The approach is conducted by describing and analyzing the contextual phenomenon of Rapaâ€™i Geleng Dance by mean of revealing the existing function in social activities dealing with the esthetic activity of the society. To analyze the function of Rapaâ€™i Geleng Dance in the time after tsunami and conflict, the researcher uses Talcott Parsons theory of â€œfunctionalism structuralismâ€ which has four concepts; they are adaptation, the realization of aims, integration, and license or the pattern development. The result of the research related to Rapaâ€™i Geleng Dance in time after tsunami and conflict has the functions on the social regulation, social integration development, new vision development, social psychotherapy, and socialization media of reconcilement, the formation of social institution structure of the North West Aceh Tribe. The Rapaâ€™i Geleng Dance is a cultural identity of the coastal area which reflects both the personal and communal life. Basically, it has a form developed through the standard pattern originally coming from the religious social activity based on the texts of Al- Qurâ€™an and Hadist. The performance of Rapaâ€™i Geleng Dance can encourage the emergence of the intensive relationship through the combination of choreographic elements of the performance which is dynamic and esthetic in society widely.Keyword: Rapaâ€™i Geleng Dance, function